Membangun Alat Deteksi Penggunaan Masker Menggunakan Arduino Pada Layanan Penerimaan Mahasiswa Baru Universitas Mahakarya Asia - Rusidi; Ristu; Defi (Universitas Mahakarya Asia, 2022)
The Covid-19 outbreak became a global pandemic after it was announced by the WHO or the World Health Organization and with its rapid spread, Covid-19 became a major topic around the world. Indonesia is no exception because the number of people infected with the Covid-19 or corona virus is increasing day by day. The central government, entering the new normal era, has begun to open activities at schools and universities by tightening the implementation of the recommended 5M health protocol, namely washing hands with soap, wearing masks, maintaining distance, avoiding crowds and limiting mobility. This is important for the government to oblige all Indonesians to wear masks when they are outside, because the spread of Covid-19 is influenced by the high mobility of the people. Build a mask detection tool using Arduino in the new student admission service of Mahakarya Asia University. The design of this mask detection device is one of the efforts to reduce the spread of the Covid-19 virus